PENGARUH KUALITAS CITA RASA, KEMASAN PRODUK DAN KEBERSIHAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN TEMPE KHAS NGRAYUN - Bety Oktavia Rahayu; Adi Santoso; Fery Setiawan (Jurnal AKTUAL, 2022)
This study aims to examine the effect of quality of taste, product packaging and product hygiene on purchasing decisions of Ngrayun Typical Tempe. The data used in this study is primary data in the form of being distributed to respondents. The population in this study were consumers of typical Ngrayun tempeh in Ponorogo district. The study population is unknown. The number of samples in the study was seen from the number of indicators multiplied by 5 to 10. In this study, the number of samples used was 70 respondents. The data analysis method used in this study uses multiple regression analysis assisted by the SPSS version 25 application. The results of this study indicate 1) the quality of taste has a significant effect on purchasing decisions for Ngrayun typical tempeh 2) Product packaging has a significant effect on purchasing decisions for Ngrayun typical tempeh. 3) Product cleanliness has a significant effect on purchasing decisions for Ngrayun typical tempeh. 4) Quality of taste, product packaging and product cleanliness significantly affect purchasing decisions for Ngrayun tempeh.